2020
DOI: 10.1507/endocrj.ej19-0436
|View full text |Cite
|
Sign up to set email alerts
|

Living alone is associated with visit-to-visit HbA1c variability in men but not in women in people with type 2 diabetes: KAMOGAWA-DM cohort study

Abstract: The purpose of this study was to evaluate the association between living alone and glycemic parameters, especially glycemic variability, in men and women with type 2 diabetes. Lifestyle factors, including living alone, were assessed by a questionnaire in this cross-sectional study. Average, standard deviation (SD), and coefficient of variation (CV) of HbA1c were calculated using the values of HbA1c, which were extracted from the medical record for 1 year. Eighteen percent of men (35/198) and 17% of women (18/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Spencer et al suggested that education and support from peers allow T2DM patients to achieve better self-management in the long term, leading to good efficacy of HbA1c control (36). A link between living alone and worse HbA1c management has also been observed in a recent study (37). Our results are consistent with those previous findings, as the mean HbA1c level in T2DM patients living alone in our study was higher than that in patients living with one or more adults.…”
Section: Discussionsupporting
confidence: 92%
“…Spencer et al suggested that education and support from peers allow T2DM patients to achieve better self-management in the long term, leading to good efficacy of HbA1c control (36). A link between living alone and worse HbA1c management has also been observed in a recent study (37). Our results are consistent with those previous findings, as the mean HbA1c level in T2DM patients living alone in our study was higher than that in patients living with one or more adults.…”
Section: Discussionsupporting
confidence: 92%
“…We analyzed the variable “living with a partner” ( Table S1 ) instead of “marital status” because the objective of selecting this variable was to assess whether living alone, given the social and emotional support provided by a partner, is associated with mental health variables, as suggested by other authors [ 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the sole diabetes sample contained a high number of patients living alone. Several studies showed that living alone is associated with visit-to-visit HbA1c variability and an independent predictor of type two diabetes in men but not women [30,31]. Our study showed that in female patients, obesity and any combinations with obesity registered the poorest HRQL on most of the scales in female clusters.…”
Section: Discussionmentioning
confidence: 40%